Role of Environmental, Social, and Governance (ESG) on the Effect of Financial Performance on Firm Value: Understanding Types of Statistical Moderation - Daromes, Fransiskus Eduardus; Jao, Robert; Synarso, Bryan Ichiro (Dinamika Akuntansi Keuangan dan Perbankan, 2026)
This study examines how environmental, social, and governance issues shape the impact of financial success on firm value. To understand the link between the variables, the legitimacy theory and signal theory are employed. The population used includes non-financial enterprises from 2019–2023 that are listed on the Indonesia Stock Exchange (IDX) and are part of the Refinitiv database. Secondary data was gathered from the Indonesia Stock Exchange, official corporate websites, and the Refinitiv database in the form of sustainability reports, annual reports, and ESG scores. The sample size is 176 company data points over 5 years, selected using the purposive sampling method. Firm value is positively and significantly impacted by financial success, according to the research findings. ESG also improves the link between firm value and financial performance, according to the study. Lastly, the study's results also show that ESG increases business value, while not significantly. These findings suggest that the study's ESG variable is a pure moderator variable. Furthermore, the implications of the research both theoretically and practically have been discussed.